PCR rates in patients with bilateral breast cancer after neoadjuvant anthracycline-taxane based-chemotherapy – A retrospective pooled analysis of individual patients data of four German neoadjuvant trials. (April 2017) - Reinisch, Mattea; Huober, Jens; von Minckwitz, Gunter; Blohmer, Jens-Uwe; Denkert, Carsten; Hanusch, Claus; Jackisch, Christian; Kümmel, Sherko; Schneeweiss, Andreas; Rhiem, Kerstin; Lederer, Bianca; Untch, Michael; et al.
Abstract: Purpose: Patients with bilateral breast cancer (BBC) are usually excluded from participating in clinical trials and little is known about the response and outcome of BBC to neoadjuvant chemotherapy compared to unilateral BC (UBC). Methods: We prospectively captured the information on patients with BBC in our database treated within four neoadjuvant chemotherapy trials and collected retrospectively the rate of pathological complete response (pCR) defined as ypT0 ypN0, ypT0/is ypN0, ypT0 ypNX, clinical and histologic parameters. Synchronous carcinoma in the contralateral breast was considered as the non-indicator lesion. Patients with UBC only treated within the same neoadjuvant trials performed the control group. Results: From the 6727 patients treated within 4 German neoadjuvant trials 119 (1.8%) patients have been identified with the diagnosis of BBC. The pCR rate (ypT0 ypN0) was 12.6% in the non-indicator lesion group versus 10.9% the indicator lesion group versus 20.9% for patients with unilateral disease (p = 0.003). There were more advanced tumor stages and positive axillary lymph nodes in the indicator lesion than in the nonindicator lesion or in UBC. In 52.5% the molecular subtype was identical between indicator and non-indicator lesion with more triple negative and HER2 positive BC in the group of UBC. The disease free survival rate (DFS) was 25.8% for patients with UBC versus 39.6% for patients with BBC. Conclusion: The selection for the indicator lesion was based on tumor size, nodal status and inclusion criteria. Patients with BBC patients had a lower pCR rate and a lower DFS. Highlights: Unilateral breast cancer has a more aggressive tumor biology. Bilateral breast cancer has a higher rate of lobular histology and more positive lymph nodes. Unilateral breast cancer has a higher rate of pCR and a better DFS. No differences were seen in OS between unilateral and bilateral breast cancer.